A comparison study between the manual and Computerized surveying systems in Engineering Surveying - H. ALI, SAMI (Iraqi Journal of Civil Engineering, 2013)
The present research aims at the comparison of the production time between the manual and computerized surveying systems. The surveying system consists of data acquisition, processing and plotting the engineering plan and contouring .The current computerised system is designed and tested using the pulse Total Station instrument GPT-2006, P.C. computer, traverse network adjustment computer programs, Auto Cad 2005, 2010 and Surfer- 9 contouring program. The results of the current field experiments showed that the computerized surveying system offers a considerable savings in the data acquisition, processing and plotting times as compared with the manual surveying system, i.e. for traversing , the reduction in the production time is up to (84%), for plan ( up to 74%) and for contouring ( up to 84%). The practical applications of the current research are in the fields of civil engineering projects ( roads, buildings, etc.), irrigation and environmental engineering schemes.